Clinical outcome after total neoadjuvant treatment (CAO/ARO/AIO-12) versus intensified neoadjuvant and adjuvant treatment (CAO/ARO/AIO 04) a comparison between two multicenter randomized phase II/III trials - Diefenhardt, Markus; Fleischmann, Maximillian; Martin, Daniel; Hofheinz, Ralf-Dieter; Piso, Pompiliu; Germer, Christoph-Thomas; Hambsch, Peter; Grützmann, Robert; Kirste, Simon; Schlenska-Lange, Anke; Ghadimi, Michael; Roedel, Claus; et al. (Radiotherapy and Oncology, 2023)
Background: Total neoadjuvant therapy (TNT) can enhance local tumor regression, but its survival bene-fits compared to intensified chemoradiotherapy (CRT) followed by adjuvant chemotherapy (CT) remain unclear.Methods: This is a secondary comparison between 607 patients treated with intensified 5-FU/Oxaliplatin neoadjuvant CRT and adjuvant CT within the experimental arm of the CAO/ARO/AIO-04 phase III trial, and 306 patients treated with TNT within the CAO/ARO/AIO-12 phase II trial. Comparison between clinical-pathological characteristics, surgical quality, and post-surgical complications were analyzed using the Pearson's Chi-squared or Mann-Whitney U test. Oncological outcome was examined with log-rank, Gray's test, and multivariate cox regression. In addition, further subgroup analyses and propensity score matching were performed to optimize the balance of baseline covariates.Findings: Patients treated with CRT followed by consolidation CT had a significantly higher rate of patho-logical complete remission (pCR) compared to patients treated within the experimental arm of the CAO/ ARO/AIO-04 trial (25.3 % vs 17.3 %, P = 0.04). Post-surgical complications were less common in the CAO/ ARO/AIO-12 trial. After a median follow-up of 46 months, clinical outcome did not differ significantly in the overall cohort, in any subgroup or after propensity score matching. In multivariate analysis, disease-free survival (DFS) was similar between the experimental arm of the CAO/ARO/AIO-04 trial and treat-ments arms of the CAO/ARO/AIO-12 trial (vs arm A: HR 0.92 [95 % CI 0.62-1.37], P = 0.69; vs arm B: HR 1.06 [95 % CI 0.72-1.58], P = 0.76).Interpretation: Notwithstanding the limitations of intertrial comparison, TNT did not improve long term oncological outcome in our study compared to the intensified neoadjuvant CRT and adjuvant CT treat-ment in the CAO/ARO/AIO-04 trial. Improved response rates after TNT offers an attractive option to explore organ preservation in selective patients with locally advanced rectal cancer.(c) 2022 Elsevier B.V. All rights reserved. Radiotherapy and Oncology 179 (2023) 109455
CRIS-Team WoS Importer:2023-03-03